OPERATIONAL SAFEGUARDING OF FRAME STRUCTURES OF FORAGE HARVESTING COMBINERS - Hneniuk, M. V. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2023)
In the article, the author presents the results of one of the research tasks, namely, the creation of controlled puffs that use for their operation the energy of elastic deformation of the unloaded system, which will make it possible to do without an external energy source. In order to achieve effectiveness and solve this problem, a three-dimensional model of the main deformable frame structure was simulated, an algorithm for calculating this model using the finite element method was developed, and an experiment was conducted based on strain gauges and the obtained experimental results were compared with the theoretical ones. The article presents the analysis of circular and meridional stresses, while in the zone of controlled tightening, the meridional stresses σmmax ’ exceed the circular stresses σtmax ’ by 2.2 times, that is, there is a redistribution of stress and the effect of the introduction of transverse controlled tightening is significantly is decreasing The system of elements of the selfpropelled forage harvester when unloading fodder plant remains, in addition, feels the stretching force. It is substantiated that a feature of such systems is that the forces applied from the outside to the controlled puffs and the resulting control loads can be in the same plane, in mutually perpendicular directions. The system of external forces applied to the structure changes over time and at the same time is a system of statically applied forces. Removal of external forces of the structure at the expense of accumulated energy returns it to its original (undeformed) state. Connecting to a deformed main structure of a controlled pull that uses internal energy can lead to residual deformations of the material of the main structure and, as a result, a violation of the technological modes of operation of the machine or the structure as a whole. Therefore, as a result, the selection of a part of the elastic energy must be carried out during the deformation between the initial and final positions of the main deformable structure, that is, between the zero and final values of the statically applied external force. The author decided to create and develop longitudinal controlled drafts for the system of elements of a self-propelled forage harvester, which are necessary to reduce the meridional stress σm, which arise in the perimeter wall when it is unloaded, and have a maximum value in the zones of influence of transverse drafts. To solve this problem, a mathematical model was built, and the dependence of the obtained expressions σt and σm was investigated, based on which, a rational design of such pulls of the system of elements of the self-propelled forage harvester was selected. The purpose of such research was to obtain designs of the system of elements of a self-propelled forage harvester, which have an increased ability to be operated, with a lower material consumption.